INFORMAL CAREGIVERS OF PATIENTS AFFECTED BY STROKE: STRATEGIES FOR REDUCTION OVERLOAD: Reduction of overload in informal caregivers of patients with stroke - Mendonça , Alysson Geraldo (2024)
Introduction: The act of daily care for patients affected by stroke is challenging and requires pluralistic knowledge, ranging from techniques related to health care, to psychological issues. Generally, these caregivers report several complaints, physical, mental and social problems in the act of caring for this patient. Objective: Identify possible strategies described in the literature that seek to reduce the physical, mental or social overload of informal caregivers of patients affected by stroke. Method: This is an integrative literature review, carried out between September 2022 and January 2023, with the following guiding question: What Can strategies described in the literature reduce the burden of informal caregivers of patients affected by stroke? The search was carried out in PubMed, SciELO and VHL databases. Results: 533 studies were found during the search, of which eight studies were selected to discuss the results. The summed total sample of informal caregivers was 687, with a mean age of 50.8 years; being 502 (73.07%) women and 185 (26.92%) men. The main strategies found in the literature were: health education in different ways (psychoeducation, guidance via telephone call, verbal guidance) and progressive muscle relaxation. Conclusion: There are strategies that aim to reduce the physical, mental and social burden of informal caregivers of patients affected by stroke. However, further studies are needed to address these strategies, especially studies that report in more detail the interventions performed.